Plug in battery electric car: jig and seat mounting brackets design and fabrication - Loh, Kiang Hun (2015)
In recent years, global warming and pollution has been an issue as it does not only impact our health but also the environment as a whole. Therefore, there has been an increase of interest in the electric vehicles as a replacement for the petroleum cars due to its carbon emission. This project aims to explore the concept of electric cars as a solution for demand for cleaner technology to reduce the harm of global warming. The project helps the students to understand the working principle of electric cars and by applying the engineering knowledge they learned in school. They are to design a Battery Electric Car of their own. The author’s task in the project involved the design and fabrication of the chassis jig and the seats mounting bracket. The side crush beam and doors were also researched, together with theories and basic design of the door for the electric car. The report aims to give a complete overview on the design and fabrication process of the chassis jig and seats mounting brackets.